Measurement and Analysis of Detecting Fish Freshness Levels Using Deep Learning Method - Anas, Dhea Fajriati; Jaya, Indra; Herdiyeni, Yeni (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2024)
Subjective and objective tests used to determine the fish deterioration process require specialized skills and time, making them inefficient for use by the general public in markets. The quality of fish products in markets is not always guaranteed, so consumers must determine their suitability. Deep learning can be used to analyze images and automatically and accurately detect the freshness of fish. This study aims to evaluate the efficiency of deep learning models in detecting fish freshness and implementing them into an Android application for public use.